Vertically Aligned Ta3N5 Nanorod Arrays for Solar‐Driven Photoelectrochemical Water Splitting. (18th September 2012) - Li, Yanbo; Takata, Tsuyoshi; Cha, Dongkyu; Takanabe, Kazuhiro; Minegishi, Tsutomu; Kubota, Jun; Domen, Kazunari
<x xml:space="preserve">Abstract</x> A vertically aligned Ta3N5 nanorod photoelectrode is fabricated by through‐mask anodization and nitridation for water splitting. The Ta3N5 nanorods, working as photoanodes of a photoelectrochemical cell, yield a high photocurrent density of 3.8 mA cm−2 at 1.23 V versus a reversible hydrogen electrode under AM 1.5G simulated sunlight and an incident photon‐to‐current conversion efficiency of 41.3% at 440 nm, one of the highest activities reported for photoanodes so far. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>